2013
DOI: 10.1007/s11548-013-0961-0
|View full text |Cite
|
Sign up to set email alerts
|

PNist: interactive volumetric measurements of plexiform neurofibromas in MRI scans

Abstract: PNist is a new method for the semiautomatic segmentation of PN lesions. Its simplicity and reliability make it unique among other state-of-the-art methods. It has the potential to become a clinical tool that allows the reliable evaluation of PN burden and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…When comparing the performance of these two segmentation methods in our study, no significant difference was observed between manual (ITK) and semiautomatic (3D Slicer) segmentation when they were applied to mMRI or DWIs, which is consistent with other studies 22 24 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When comparing the performance of these two segmentation methods in our study, no significant difference was observed between manual (ITK) and semiautomatic (3D Slicer) segmentation when they were applied to mMRI or DWIs, which is consistent with other studies 22 24 .…”
Section: Discussionsupporting
confidence: 91%
“…Morphological imaging (e.g., CT, MR T1WI or T2WI) and functional imaging (e.g., MR DWI and positive emission tomography, PET) have been used for the delineation of GTV measurements 10 13 18 23 24 . Among these imaging modalities, MRI provides the best soft tissue contrast and spatial resolution compared to other modalities 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The time necessary for a trained imaging scientist to process the images and delete normal anatomy took on average 6 min compared to an average of 18 min for manual volumetric analysis. Furthermore, Weizman et al determined that for complex cases, up to 35 min per case would be required for manual segmentation 13 . If one expands this to the typical case load encountered by radiologists at our institution, this amounts to 0.007-0.014 FTE, or $3500-7000/case in annualized cost savings.…”
Section: Discussionmentioning
confidence: 99%
“…This approach, which overcomes the slice limitations of previous investigators, still requires that a trained expert identify each tumor in the image volume. Finally, Weizman et al 13 also uses a STIR histogram matching algorithm which requires a one-time training requiring manual volumetric analysis of a tumor and identifying of a small frame including most of the tumor and a large frame which includes tumor and background. In the segmentation phase, the user is required to scribble over the tumor, which can then propagate in 3D space; however, like all the described methods, manual error correction of STIR hyper-intense normal structures adjacent to tumor is required.…”
Section: Discussionmentioning
confidence: 99%
“…This approach, which overcomes the slice limitations of previous investigators, still requires that a trained expert identify each tumor in the image volume. Finally, Weizman et al 13 also uses a STIR histogram matching algorithm which requires a one-time training requiring manual volumetric analysis of a tumor and identifying of a small frame including most of the tumor and a large frame which includes tumor www.nature.com/scientificreports/ and background. In the segmentation phase, the user is required to scribble over the tumor, which can then propagate in 3D space; however, like all the described methods, manual error correction of STIR hyper-intense normal structures adjacent to tumor is required.…”
Section: Discussionmentioning
confidence: 99%